Edukasi Pencegahan Covid 19 Varian Xbb Pada Anak Dan Remaja Dipanti Asuhan Kasebeng Bentiring - Diniarti, Fiya; Metasari, Des; Afrianti, Mariza (Jurnal Dehasen Mengabdi, 2023)
Corona virus is a virus that attacks the respiratory tract and causes high fever, cough, flu, shortness of breath and sore throat. The coronavirus can cause death in the world. In 2022 in Indonesia as many as 6,186 cases of covid 19, until now cases of sub-variants BA4 and BA5 still dominate, to overcome this problem, the solution provided is education on the prevention of the XBB variant of covid 19 in children and adolescents at the Kasebeng Bentiring Orphanage. The method of service of this activity starts from the preparation, implementation and evaluation of activities. The implementation time starts from November to December 2023. The results of this activity are an increase in the knowledge of children and adolescents in preventing and breaking the transmission of Covid 19 XBB variant specifications. Community service about education on preventing the transmission of the XBB variant of Covid-19 is effective in preventing and breaking the chain of transmission through increasing knowledge, because the higher a person's knowledge about the transmission of the XBB Variant of Covid-19, the better his behavior will be in preventing the transmission. All participants participated in educational activities from beginning to end and the results of which there was an increase in knowledge about the transmission of Covid-19, reflected in the increase in postest results compared to pre-tests and participants were able to answer the questions asked and were very enthusiastic in the discussion. Based on the results of community service activities, it can be suggested to the management of the orphanage to cooperate with related parties in increasing the knowledge of the children of the orphanage, and not to adhere to azaz kebersaam for tableware, sleeping utensils and toiletries even though it is in the same place (Panti).